Kriminalisasi Perempuan Pekerja Seks Komersial dalam Perluasan Pasal Zina RUU KUHP - Suryani, Leony Sondang; Purwanti, Ani (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2018)
Prostitution practice has hitherto been a niche part of modern civilization whereby Indonesia is no exception. As prostitution is commonly perceived as a ragtag phenomenon which would stain the existing moral norms and social dignity, it is certain that there is an obligation by the government to control and regulate such practice. However, the regulation upon prostitution must be taking considerations, in respect of anti-discrimination, equality, and humanistic treatments towards the prostitutes into account. Yet, it is often, if not always, that this presumption has been taken for granted and instead such regulation can be draconian towards sex-workers. This article explores such a problem in the case of Indonesia’s new Criminal Code Bill –which ought to replace the existing Criminal Code-. The new Criminal Code Bill –which currently is undergoing a seemingly hasty legislation process in the House of Representatives- possess such draconian law potential on this regard due to its adultery provision which has been broadened to the extent of possible penalization against sexual acts by unmarried pairs. This article presents an analysis on the possible implication of Criminal Code Bill –specifically the adultery part thereof- upon sex workers through socio-legal method whereby the combination of normative legal approach and social research method are applied. This article contends that such broadly defined adultery provision can lead to an unjust penalization –thus miscarriage of justice- of sex workers by whom the law ought to treat as victims of exploitation and sexual deception instead of perpetrators of crime.